Understanding pop-up stores through passion and practice - Boustani, Ghalia (Routledge, 2025)
"Whether physical or virtual, heritage brand or start-up, pop-up stores are everywhere: this book provides the 'why, what, and how' for entrepreneurs and established brands to capitalize on this exciting format. This book guides readers through the 20-year evolution of pop-up stores, their integration into overarching brand strategies, and the practical ins and outs of pop-up store development, offline or online. Insights from over 90 recent case studies further illuminate the tools that need to be considered and guidelines to be followed for pop-up store success, including distribution, communications strategy, atmospheric design, budgeting, events, and legal considerations. Brand managers, consultants, retail professionals, and retail marketing and management students will benefit from this engaging and reliable guide, learning that behind pop-up stores' sparkly and ephemeral image lies the utmost attention to detail"--